Estrogen Receptors and Their Implications in Colorectal Carcinogenesis - Caiazza, Francesco; Ryan, Elizabeth J.; Doherty, Glen; Winter, Desmond C.; Sheahan, Kieran (Frontiers in Oncology, 2015)
Upon binding their cognate receptors, ERα (ESR1) and ERβ (ESR2), estrogens activate intracellular signaling cascades that have important consequences for cellular behavior. Historically linked to carcinogenesis in reproductive organs, estrogens have also been implicated in the pathogenesis of different cancer types of non-reproductive tissues including the colon. ERβ is the predominant estrogen receptor expressed in both normal and malignant colonic epithelium. However, during colon cancer progression ERβ expression is lost, suggesting estrogen signaling may play a role in disease progression. Estrogens may in fact exert an anti-tumor effect through selective activation of pro-apoptotic signaling mediated by ERβ, inhibition of inflammatory signals and modulation of the tumor microenvironment. In this review we analyze the estrogen pathway as a possible therapeutic avenue in colorectal cancer, we report the most recent experimental evidence to explain the cellular and molecular mechanisms of estrogen-mediated protection against colorectal tumorigenesis, and we discuss future challenges and potential avenues for targeted therapy.